Restricted modes: Social media, content classification and LGBTQ sexual citizenship. (May 2021) - Southerton, Clare; Marshall, Daniel; Aggleton, Peter; Rasmussen, Mary Lou; Cover, Rob
In the context of recent controversies surrounding the censorship of lesbian, gay, bisexual, transgender and queer online content, specifically on YouTube and Tumblr, we interrogate the relationship between normative understandings of sexual citizenship and the content classification regimes. We argue that these content classification systems and the platforms' responses to public criticism both operate as norm-producing technologies, in which the complexities of sexuality and desire are obscured in order to cultivate notions of a 'good' lesbian, gay, bisexual, transgender or queer sexual citizen. However, despite normative work of classification seeking to distinguish between sexuality and sex, we argue that the high-profile failures of these classification systems create the conditions for users to draw attention to, rather than firm, these messy boundaries.